If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) + 2(x + 5) = 21 Reorder the terms: 3(-3 + x) + 2(x + 5) = 21 (-3 * 3 + x * 3) + 2(x + 5) = 21 (-9 + 3x) + 2(x + 5) = 21 Reorder the terms: -9 + 3x + 2(5 + x) = 21 -9 + 3x + (5 * 2 + x * 2) = 21 -9 + 3x + (10 + 2x) = 21 Reorder the terms: -9 + 10 + 3x + 2x = 21 Combine like terms: -9 + 10 = 1 1 + 3x + 2x = 21 Combine like terms: 3x + 2x = 5x 1 + 5x = 21 Solving 1 + 5x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5x = 21 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = 21 + -1 5x = 21 + -1 Combine like terms: 21 + -1 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 7-3x=-23 | | x(2x-5)(x+6)= | | 2/3x=-7 | | 5/6/8 | | n/9-4=11 | | 125x+3=52x+4 | | 0.4p-2=0.8p-3 | | 8x+2(x-9)=82 | | -7x=-4 | | 93x=27 | | 0=5.1x+0.3x | | 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 |